Process Parameter Effects on Powder Mixed EDM Machining Characteristics Using Biocompatible Ti-6Al-4V Alloy - Tiwari, Diwaker; Srivastava, Ashok Kumar (International Journal of Experimental Research and Review, 2024)
This study examines how various process parameters affect the machining properties of a bio-compatible Ti-6Al-4V alloy using PMEDM with silicon carbide (SiC) powder. The parameters investigated include peak current, pulse on/off time, powder concentration, and voltage gap. The study analyzed their effects on material removal rate (MRR), tool wear rate (TWR), surface roughness (SR), and surface morphology. A central composite design was used in the tests to make empirical models that use response surface methods to link the process parameters to the machining results. It is found that the Pulse current and Ton influence the material removal rate and the surface roughness significantly. The powder concentration also impacts PMEDM's machining performance. The Scanning electron microscopic images reveal the effect of powder seen in the machined components. The crater, micro cracks and machining marks can be seen in the SEM images. The surface integrity is correlated with the output parameters of surface roughness. The developed mathematical models effectively predict and optimize the machining properties of Ti-6Al-4V alloy using PMEDM with SiC powder. This research offers valuable insights for applying PMEDM in the fabrication of biomedical implants and devices made from Ti-6Al-4V alloy.